Spatially resolved performance and degradation in a perfluorinated anion exchange membrane fuel cell. (20th February 2022) - Divekar, Ashutosh G.; Gerhardt, Michael R.; Antunes, Christopher M.; Osmieri, Luigi; Yang-Neyerlin, Ami C.; Weber, Adam Z.; Pivovar, Bryan S.; Bender, Guido; Herring, Andrew M.
Abstract: Anion exchange membrane fuel cells may enable future operation with non-precious metal-based catalysts. These systems have a delicate sensitivity to operating conditions such as humidification levels and the presence of CO2 in the air oxidant stream. We present spatially resolved in-situ performance results that shed light on phenomena that are unique to anion exchange membrane fuel cells. For cell construction, a highly conductive perfluorinated anion exchange polymer was used as the membrane and the material in powder form as the ionomer. Experiments were conducted to investigate the effects of humidification, fuel/oxidant concentration, and carbonation effects on the performance and its distribution in the cell. The results indicated that (i) dry conditions at the cathode have a stronger effect than at the anode on overall cell performance, (ii) performance significantly suffered when humidification was below 90%, (iii) fuel and oxidant dilution effects lead mass-transport losses and were stronger than flow rate effects, (iv) CO2 in the cathode feed stream creates an equilibration disparity between the inlet and outlet sections and CO2 purging is affected by flooding conditions, and (v) after >500 h of operation, performance deteriorates predominantly at the inlet. Abstract : Image, graphical abstract .